"Como Si Nada": Enduring Violence and Diabetes among Rural Women in Southern Mexico. Issue 3 (3rd April 2018) - Montesi, Laura
ABSTRACT: Rural women in Southern Mexico link their diabetes to distressful life experiences rooted in ordinary violence. While much has been written on the use that diabetes sufferers make of their morbid condition as an idiom of distress, I investigate the personal and social effects that such an idiom has on women. As I illustrate, diabetes reflects an ambivalence that helps women to speak about the unspeakable and, at the same time, reinforces their ideas of culpability, namely that they are to blame for both the gendered violence that they endure and the diabetes from which they suffer.